Effected Proteins in Apple and Erwinia amylovora Interactions - Kubilay Kurtulus Bastas; Ayşegül - Gedük (Turkish Journal of Agriculture: Food Science and Technology)
Fire blight disease caused by Erwinia amylovora can infect almost 140 plants of the Rosaceae family and poses a great threat to pome fruits growing all over the world. It needs amylovoran and Type III secretion systems (T3SS) to cause disease in host plants. AmsB, AmsD, AmsE, AmsF, AmsG, AmsJ, AmsI and AmsK proteins are involved in the binding of different galactose, glucuronic acid and pyruvyl subunits to the lipid carrier to form an amylovoran unit. T3SS proteins secreted by E. amylovora are HrpA HrpN, HrpW, AvrRpt2EA, HopC1 and DspA/E. DspA/E, the sole effector of E. amylovora, is secreted by during the formation of pilus T3SS. The chaperone protein of E. amylovora is DsB/F, which is in the IA class. EopB (outer membrane protein) has been characterized as one of the secretory proteins of E. amylovora. In addition to the harpins, the pathogenicity protein DspE and OrfB proteins are secreted via the Hrp-secretory system of E. amylovora. E. amylovora forms a Hrp pilus, which is produced by the structural protein HrpA. Genes encoding antimicrobial proteins cloned and expressed in apples and pears for impart resistance to the pathogen, attacin E are cecropins and lysozymes. The expression of PR2, PR5 and PR8 proteins is increased with E. amylovora infection in apple. Again, the HIPM protein in apples interacts with the E. amylovora HrpN protein, and the HIPM protein is found in higher amounts in flowers than leaves and shoots. In addition, four apple proteins (DIPMs) that interact with E. amylovora effector protein DspA/E have an effective role in endurance. In order to understand the interaction between the plant and the pathogen, it will be possible to understand the proteins that recognize the pathogen in the host, as well as the signal system and plant defense mechanism resulting from the infection. In this study, the roles of proteins associated with pathogenesis as a result of infection of E. amylovora in apples were tried to be revealed.